1983
DOI: 10.1002/app.1983.070281112
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal degradation of cis‐1,4‐polyisoprene vulcanizates

Abstract: SynopsisThe isothermal degradation of high cis-l,4-polyisoprene Vulcanizates having different crosslinking structures was investigated by a measurement of weight loss of sample, I R and NMR, gel permeation chromatography (GPC), and gas chromatography (GC). The degradation behavior of dicumy peroxide-cured sample is similar to that of the uncrosslinked one. On the other hand, a sulfur-cured sample is very different from the other samples. At the initial stage of the degradation, weight loss in this sample is fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Limonene (t R = 22.71 min) is the one present in the highest concentration. Several researchers have reported that limonene decreases as the pyrolysis temperature is increased [8,[34][35][36]. Table 5 also shows a very important decrease of limonene concentration with temperature (from ≈21 to 3%).…”
Section: Gas Chromatography/mass Spectroscopy (Gc/ms) Analysismentioning
confidence: 81%
“…Limonene (t R = 22.71 min) is the one present in the highest concentration. Several researchers have reported that limonene decreases as the pyrolysis temperature is increased [8,[34][35][36]. Table 5 also shows a very important decrease of limonene concentration with temperature (from ≈21 to 3%).…”
Section: Gas Chromatography/mass Spectroscopy (Gc/ms) Analysismentioning
confidence: 81%
“…Then the reactor was purged before experiments by the flow of N 2 gas of 4 L/min for 5 min to remove air inside. The reactor heater (power system) and LPG burner were switched on, and the sample was heated at heating rates of [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] o C/min to a desired value of temperature of either 375, 425, 475, 525 or 575 o C and hold at that temperature for 50 min, or no further visible vapor product coming out. Nitrogen gas was supplied in order to maintain the inert atmosphere in the reactor and also to sweep away the pyrolyzed vapor product to the condensers.…”
Section: Methodsmentioning
confidence: 99%
“…Tamura et al (19) have also shown that isoprene and D,L-limonene are formed in high concentration in natural rubber pyrolysis and they suggest that they are produced by depolymerisation from polymer radicals, by β-scission of the double bond. The polymer radicals are liable to form six-membered rings, especially under mild pyrolysis Heat conditions and therefore the D,L-limonene is formed predominantly at lower temperature.…”
Section: Thementioning
confidence: 99%
See 1 more Smart Citation
“…It has been known that tire pyrolysis oil contains DLlimonene produced by depolymerization of natural rubber occurring by b-scission at double bonds [1] or by monomer recombination via a Diesel-Alder reaction [2]. The major products of the isoprene dimer species are DL-limonene [1-methyl-4-(1-methylethenyl)-cyclohexene] and 1,4-dimethyl-4-vinylcyclohexene.…”
Section: Introductionmentioning
confidence: 99%